ANALISIS PEMBUKAAN REKENING ONLINE TERHADAP KEPUASAAN NASABAH BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU DRAMAGA BOGOR - Kurniasih, Eneng; Thantawi, Tubagus Rifqy; Anwar, Miftakhul (SAHID BANKING JOURNAL, 2023)
Online account opening is regulated in Financial Services Authority Regulation (POJK) Number 12/PJOK03/2018 concerning the Implementation of Digital Banking Services by Commercial Banks. The Financial Services Authority regulates the provision of digital services for sharia and conventional banks. With these regulations, Bank Syariah Indonesia can provide digital or online services based on existing regulations. This digital or online service provided by Bank Syariah Indonesia aims to make things easier and save customers' time. In connection with this, the aim of this research is to analyze opening an online account on customer satisfaction at Bank Syariah Indonesia, Dramaga Bogor Branch Office. The research method used is a quantitative method. The variables in this research are Service Quality (X1) and Information Quality (X2) and Customer Satisfaction (Y). The research uses SPSS Version 23 tools. The results of this research conclude that service quality and information quality have a positive effect on customer satisfaction.